Morphological trends in the molars of fossil rodents from the Fayum Depression, Egypt - Lewis, Patrick J.; Simons, Elwyn L. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2007)
While many of the mammalian taxa from the Fayum of Egypt, such as the primates and hyraxes, have been well-studied, little is known about the rodents. Species described to date have all been referred to the endemic family Phiomyidae. Many rodent species from this family have been named and their importance to biogeography addressed, but what this fauna can reveal about the palaeoenvironment of the Fayum has yet to be determined. The study of palaeoenvironmental trends begins with a general examination of species diversity and morphology of the specific rodent lineages. A statistical analysis of available molar measurements of Fayum rodents estimates general size and shape trends and changes in rodent diversity through the stratigraphic sequence of the Fayum. This analysis finds stability in species diversity and an increase in the average body size of taxa using molar length as an estimate of body size. The body size pattern of the rodents is similar to the pattern found among the Fayum primates. Analysis of molar length and width has been performed to test whether these variables could discriminate accurately between taxa. If molars that are too worn to be identified by cusp pattern can be identified confidently based on length and width, more specimens could be included in future analyses and a more accurate depiction of the small mammal fauna attained. Length is significantly different between most of the species, and several species can be identified by length and width alone. Length and width relationships were consistent for species within the same genus.